Legacy : a novel - Steel, Danielle (New York : Dell, 2011)
Weaves together the stories of Brigitte Nicholson, a modern-day writer assisting her mother with a family genealogy project, and Brigitte's ancestor Wachiwi, a daring young Sioux woman on an incredible journey to the French court in the eighteenth century
Keywords: Genealogy -- Fiction; Family secrets -- Fiction; Indians of North America -- History -- 18th century -- Fiction; Indians of North America -- South Dakota -- Fiction; Indian women -- Fiction